Effect of exercise training interventions on energy intake and appetite control in adults with overweight or obesity: A systematic review and meta‐analysis - Beaulieu, Kristine (2021)
This systematic review examined the impact of exercise training interventions on energy intake (EI) and appetite control in adults with overweight/obesity (≥18 years including older adults). Articles were searched up to October 2019. Changes in EI, fasting appetite sensations, and eating behavior traits were examined with random effects meta-analysis, and other outcomes were synthesized qualitatively. Forty-eight articles were included (median [range] BMI = 30.6 [27.0-38.4] kg/m2 ). Study quality was rated as poor, fair, and good in 39, seven, and two studies, respectively. Daily EI was assessed objectively (N = 4), by self-report (N = 22), with a combination of the two (N = 4) or calculated from doubly labeled water (N = 1). In studies rated fair/good, no significant changes in pre-post daily EI were found and a small but negligible (SMD < 0.20) postintervention difference when compared with no-exercise control groups was observed (five study arms; MD = 102 [1, 203] kcal). There were negligible-to-small pre-post increases in fasting hunger and dietary restraint, decrease in disinhibition, and some positive changes in satiety and food reward/preferences. Within the limitations imposed by the quality of the included studies, exercise training (median duration of 12 weeks) leads to a small increase in fasting hunger and a small change in average EI only in studies rated fair/good. Exercise training may also reduce the susceptibility to overconsumption (PROSPERO: CRD42019157823).